Case report: Tibial and fibular osteochondroma as an unusual cause of popliteal artery entrapment syndrome [version 1; peer review: 1 approved, 1 approved with reservations] - De Oliveira Mariúba, Jamil Victor [UNESP]; Lima Sobreira, Marcone [UNESP]; Bonetti Yoshida, Winston [UNESP]; De Oliveira Mariúba, Eduardo Savio [UNESP]; De Almeida Rollo, Hamilton [UNESP]; Moura, Regina [UNESP]; Bertanha, Matheus [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Farres Pimenta, Rafael Elias [UNESP]; Bueno De Camargo, Paula Angeleli [UNESP]; Silva Secondo, Mariana Thais [UNESP] (F1000Research, 2018)
Background: Osteochondroma, or osteocartilaginous exostosis, is the most common benign neoplasm of bone, and accounts for 20-50% of all benign tumors. Vascular complications associated with osteochondromas are rare, and include pseudoaneurysm formation, vessel occlusion and vessel displacement. To date, only two cases of popliteal artery entrapment syndrome (PAES) caused by an isolated fibular osteochondroma have been reported. Case Report: This report describes a unique case of PAES. A 33-year-old woman had a history of multiple osteochondroma, including of the proximal tibia and fibula on the left, diagnosed at age two years and monitored clinically by an orthopedist. The patient presented at our facility with a one-year history of a progressive intermittent claudication, left-sided toe pain and pallor in cold weather. After a complete evaluation, we diagnosed an arterial occlusion of the left popliteal artery. We tried several attempts of revascularization, by different forms, without success. The case went to amputation surgery. Conclusion: We consider this an important case because, although the association of osteochondroma and PAES is rare, physicians should consider it early to avoid acute vascular complications. Moreover, to date, we believe this is the first description of a PAES related with multiple osteochondroma.
Keywords: Fibula; Osteochondroma; Popliteal artery; Popliteal entrapment syndrome; Tibia